Bright light therapy as a non-pharmacological treatment option for multiple sclerosis-related fatigue: A randomized sham-controlled trial. Issue 4 (October 2022) - Voggenberger, Lisa; Böck, Marion; Moser, Doris; Lorbeer, Gudrun; Altmann, Patrick; Leutmezer, Fritz; Berger, Thomas; Seidel, Stefan
Background: Fatigue is a common symptom in people with multiple sclerosis (pwMS) that significantly impairs quality of life. Bright light therapy may be a cheap treatment option with little to no adverse events. Objectives: To evaluate the effectiveness of bright light therapy as a treatment option for MS-related fatigue. Methods: This was randomized sham-controlled trial including 26 pwMS with a Fatigue Severity Scale (FSS) Score ≥36. Participants were assigned to receive either bright white light therapy ( n  = 13) or dim red light (sham-intervention; n  = 13). Participants used the respective intervention for 30 min each morning for two weeks, followed by a two-week washout period. The primary endpoint was the difference in FSS scores following light treatment as calculated by analysis of covariance. Results: There was no significant difference in FSS (F(1, 23) = 2.39, p  = .136, partial ⴄ 2  = .094). However, FSS scores generally improved over the course of the study in a clinically relevant manner. Conclusion: Bright light therapy decreased FSS scores over the course of this study. However, this effect was not significant in comparison to a sham intervention.